Acute symptomatic vitreous floaters assessed with ultra-wide field scanning laser ophthalmoscopy and spectral domain optical coherence tomography - Gisung Son; Joonhong Sohn; Mingui Kong (Scientific Reports, 2021)
Abstract To describe the eyes with vitreous floaters and to analyze the development of acute symptomatic posterior vitreous detachment (PVD). A retrospective review of medical records was performed on patients with the vitreous floater developed for the first time of their life. Peripapillary vitreous opacity (pVO) was searched in Ultra-wide field (UWF) scanning laser ophthalmoscopy and PVD stage was assessed through spectral-domain optical coherence tomography (SD-OCT). 196 patients (55 males and 141 females), who were 58.4 (± 9.1) years old, visited a retinal clinic 9.4 (± 9.1) days after they experienced vitreous floaters. In 196 eyes, pVO was noticed in 122 eyes (62.2%) at UWF. In 106 eyes where SD-OCT data were available, PVD was noticed in 100 eyes (94.3%). Symptomatic eyes showed more advanced stage of PVD (p < 0.001) than symptom free eyes. Eyes with floaters were more myopic (− 0.7 ± 2.2D vs − 0.5 ± 1.9D, p = 0.02), and had lower intraocular pressure (IOP) (14.7 ± 3.2 mmHg vs 15.2 ± 3.0 mmHg, p = 0.02) than the other symptom free eyes. In patients with first floater symptoms, PVD was in progress in most of the eyes not only the symptomatic eyes but also on the contralateral symptom free eyes. Eyes with vitreous floaters were more myopic and had lower IOP than the opposite symptom free eyes.